The Absence of Toll-Like Receptor 4 Mildly Affects the Structure and Function in the Adult Mouse Retina - Noailles, Agustina; Kutsyr, Oksana; Maneu, Victoria; Ortuño-Lizarán, Isabel; Campello, Laura; de Juan, Emilio; Gómez-Vicente, Violeta; Cuenca, Nicolás; Lax, Pedro (Frontiers in Cellular Neuroscience, 2019)
The innate immune Toll-like receptor (TLR) family plays essential roles in cell proliferation, survival and function of the central nervous system. However, the way in which TLRs contribute to the development and maintenance of proper retinal structure and function remains uncertain. In this work, we assess the effect of genetic TLR4 deletion on the morphology and function of the retina in mice. Visual acuity and retinal responsiveness were evaluated in TLR4 knockout and wild type C57BL/6J control mice by means of an optomotor test and electroretinography, respectively, from P20 to P360. Retinal structure was also analyzed in both strains using confocal and electron microscopy. ERG data showed impaired retinal responsiveness in TLR4 KO mice, in comparison to wild type animals. The amplitudes of the scotopic a-waves were less pronounced in TLR4-deficient mice than in wild-type animals from P30 to P360, and TLR4 KO mice presented scotopic b-wave amplitudes smaller than those of age-matched control mice at all ages studied (P20 to P360). Visual acuity was also relatively poorer in TLR4 KO as compared to C57BL/6J mice from P20 to P360, with significant differences at P30 and P60. Immunohistochemical analysis of retinal vertical sections showed no differences between TLR4 KO and C57BL/6J mice, in terms of either photoreceptor number or photoreceptor structure. Horizontal cells also demonstrated no morphological differences between TLR4 KO and wild-type mice. However, TLR4 KO mice exhibited a lower density of bipolar cells (15% less at P30) and thus fewer bipolar cell dendrites than the wild type control mouse, even though both confocal and electron microscopy images showed no morphologic abnormalities in the synaptic contacts between the photoreceptors and second order neurons. Microglial cell density was significantly lower (26% less at P30) in TLR4 KO mice as compared to wild-type control mice. These results suggest that TLR4 deletion causes functional alterations in terms of visual response and acuity, probably through the loss of bipolar cells and microglia, but this receptor is not essential for the processing of visual information in the retina.